Antycypacyjna rola przepisów planu miejscowego w systemie zapewniania bezpieczeństwa ludności w stanie klęski żywiołowej - Tabernacka, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Legal order should provide system of regulations with the ability to counteract combat negative effects of natural disasters at their earliest stage. This is particularly important due to the legal obligation to ensure safety of the population. The legislation enabling to anticipate the negative consequences associated with the occurrence of natural disasters is a local plan, which should be a part of the system ensuring safety of the population within the municipality
Keywords: akty prawa miejscowego; klęski żywiołowe; polityka administracyjna; prawa własności; prewencja